Synergistic technologies for a circular economy: upcycling waste plastics and biomass - Ahmed I., Osman; Mahmoud, Nasr; Chukwunonso O., Aniagor; Mohamed, Farghali; Hung, Mee Mee; Bridgid Chin, Lai Fui; Ziqiang, Sun; Serene Lock, Sow Mun; Eduardo A., López-Maldonado; Yiin, Chung Loong; Charles E., Chinyelu; Abid Salam, Farooqi; et al. (Springer Nature, 2024)
The urgent need for sustainable waste management has led to the exploration of upcycling waste plastics and biomass as viable solutions. In 2018, global plastic production reached 359 million tonnes, with an estimated 12000 million tonnes projected to be delivered and disposed of in landfills by 2050. Unfortunately, current waste management practices result in only 19.5% of plastics being recycled, while the rest is either landfilled (55%) or incinerated (25.5%). The improper disposal of plastics contributes to issues such as soil and groundwater contamination, air pollution, and wildlife disturbance. On the other hand, biomass has the potential to deliver around 240 exajoules of energy per year by 2060. However, its current utilization remains relatively small, with only approximately 9% of biomass-derived energy being consumed in Europe in 2017. This review explores various upcycling methods for waste plastics and biomass, including mechanical, chemical, biological, and thermal approaches. It also highlights the applications of upcycled plastics and biomass in sectors such as construction, packaging, energy generation, and chemicals. The environmental and economic benefits of upcycling are emphasized, including the reduction of plastic pollution, preservation of natural resources, carbon footprint reduction, and circular economy advancement.